Species-Wide Variation in Shoot Nitrate Concentration, and Genetic Loci Controlling Nitrate, Phosphorus and Potassium Accumulation in Brassica napus L. - Alcock, Thomas D.; Havlickova, Lenka; He, Zhesi; Wilson, Lolita; Bancroft, Ian; White, Philip J.; Broadley, Martin R.; Graham, Neil S. (Frontiers in Plant Science, 2018)
Large nitrogen, phosphorus and potassium fertiliser inputs are used in many crop systems. Identifying genetic loci controlling nutrient accumulation may be useful in crop breeding strategies to increase fertiliser use efficiency and reduce financial and environmental costs. Here, variation in leaf nitrate concentration across a diversity population of 383 genotypes of Brassica napus was characterised. Genetic loci controlling variation in leaf nitrate, phosphorus and potassium concentration were then identified through Associative Transcriptomics using single nucleotide polymorphism (SNP) markers and gene expression markers (GEMs). Leaf nitrate concentration varied over 8-fold across the diversity population. A total of 455 SNP markers were associated with leaf nitrate concentration after false-discovery-rate (FDR) correction. In linkage disequilibrium of highly associated markers are a number of known nitrate transporters and sensors, including a gene thought to mediate expression of the major nitrate transporter NRT1.1. Several genes influencing root and root-hair development co-localise with chromosomal regions associated with leaf P concentration. Orthologues of three ABC-transporters involved in suberin synthesis in roots also co-localise with association peaks for both leaf nitrate and phosphorus. Allelic variation at nearby, highly associated SNPs confers large variation in leaf nitrate and phosphorus concentration. A total of five GEMs associated with leaf K concentration after FDR correction including a GEM that corresponds to an auxin-response family protein. Candidate loci, genes and favourable alleles identified here may prove useful in marker-assisted selection strategies to improve fertiliser use efficiency in B. napus.